My status as an assassin obviously exceeds the hero's. 3 - Akai, Matsuri; Akai, Matsuri; Black, Clint (Seven Seas Entertainment, 2020)
Hunting for the strength to avenge his murdered friend, Akira set his sights on reaching the bottom of an ancient labyrinth. There, Akira discovers a huge, talking black cat -- a servant of the Demon King and unexpected ally. After they form a pact to join forces, a magic circle whisks Akira away to the home of his new companion Emilia, the land of the elves. There, unexpected secrets about Emilia's history come into dangerous focus!